Iustitia and Corruptio in Liber Constitutionum sive Lex Gundobada - Valentinova, Dorothea (Studia Ceranea, 2022)
After 476, Flavius Gundobadus, King of the Burgundians (473–516), sought ways and means to consolidate and strengthen his power, including through legal regulation of the relations between the Burgundians themselves, on the one hand, and between the Burgundians and the Gallo-Romans, on the other. Thus, Liber Constitutionum sive Lex Gundobada was issued, the main purpose of which is the legal regulation of the complex relations in the kingdom, through a codification of the preserved customary law – an embodiment of tribal traditions, practices, and customs, with reasonable use of Roman legal ideas, notions, and norms. The translation and analysis of selected provisions from Lex Gundobada in this paper show the extent to which the Burgundians perceived, received, adopted, and adapted some of the most valuable Roman legal and moral rules and principles, especially the Roman concepts of iustitia and corruptio, and how the rights of both the Burgundians and the Romans were regulated and protected through them. Lex Burgundionum is part of a series of legal Barbarian codes, compiled, adapted, published, and applied in the Barbarian regna between the 5th and 9th centuries. These codes are one of the significant and true sources for the historical reconstruction of the socio-political, socio-cultural, and legal-administrative transition from the late Roman Empire to the German kingdoms and early medieval Europe. They manifest how historically the arena of clashes, confrontations, and wars between Romanitas and Barbaritas gradually became a contact zone of legal reception, of cultural, legal, and socio-political influences, from which a new world will be born, a successor to the old ones, and a new legal system – the Romano-Germanic one.